Assignment: [tex]\bold{Simplify \ Equation: \ \left(2x+3\right)\left(3x-5\right)}[/tex]
<><><><><>
Answer: [tex]\boxed{\bold{6x^2-x-15}}[/tex]
<><><><><>
Explanation: [tex]\downarrow\downarrow\downarrow[/tex]
<><><><><>
[ Step One ] Apply Foil Method
Note: [tex]\bold{Foil \ Method: \ \left(a+b\right)\left(c+d\right)=ac+ad+bc+bd}[/tex]
[tex]\bold{a=2x,\:b=3,\:c=3x,\:d=-5}[/tex]
<><><><><>
[tex]\bold{2x\cdot \:3x+2x\left(-5\right)+3\cdot \:3x+3\left(-5\right)}[/tex]
[ Step Two ] Apply Addition / Subtraction Rules
Note: [tex]\bold{Addition \ / \ Subtraction \ Rules: \ +\left(-a\right)=-a}[/tex]
[tex]\bold{2\cdot \:3xx-2\cdot \:5x+3\cdot \:3x-3\cdot \:5}[/tex]
[ Step Three ] Simplify [tex]\bold{2\cdot \:3xx-2\cdot \:5x+3\cdot \:3x-3\cdot \:5}[/tex]
[tex]\bold{6x^2-x-15}[/tex]
<><><><><><><>
[tex]\bold{\rightarrow Mordancy \leftarrow}[/tex]